Selenato e selenito na produção, nutrição mineral e biofortificação com selênio em cultivares de alface - Ramos, Sílvio Júnio; Faquin, Valdemar; de Almeida Jr., Hilário [UNESP]; Ávila, Fabrício William; Guilherme, Luiz Roberto Guimarães; Bastos, Carla Elisa Alves; Ávila, Patrícia Andressa (FapUNIFESP (SciELO), 2011)
Selenium is an important antioxidant element associated with physiological processes in plants, microorganisms, animals, and humans. However, its mode of action and essentiality in plants are still disputed. In Brazil, information on Se in agricultural crops is extremely scarce, though there are indications that low levels of Se are being consumed by the population. The objective of this study was to evaluate the effect of selenate and selenite on yield, mineral nutrition and biofortification with Se of lettuce cultivars. The experiment was arranged in a completely randomized factorial design 5 x 3 x 2, with five lettuce cultivars (Maravilha de Verão, Rafaela, Great Lakes, Veneranda, and Vera), three Se concentrations (0, 10 and 20 μmol L-1) and two forms of Se (selenate and selenite), with four replicates. Results indicate that selenate application is more appropriate for biofortification of lettuce cultivars, while the effect of selenite proved to be more toxic. The application of selenate results in increased S shoot concentrations, while selenite reduced P concentrations, and both Se forms decreased micronutrient concentrations. No genotypic variation among lettuce cultivars was observed for Se concentration, and little variation was observed for shoot dry matter yield and S, Mg, Mn, and Fe levels.
Selenate and selenite on yield, mineral nutrition and biofortification with selenium in lettuce cultivars
Keywords: Lactuca sativa; Macronutrient; Micronutrient; Selenium concentration